The Role of Peer-group Influence and Neurobiological Factors in Internet Gaming Disorder - Tesaviani Kusumastiwi (HM Publisher, 2020)
Abstract Internet game disorder (IGD) is characterized as an excessive and uncontrolled game designed for functional problems or difficulties. During the last discussion, uncontrolled internet games have resulted in public health and social problems around the world. Although brave games are more accessible in young adulthood, brave game disturbances are more experienced by teens. Teenagers and young adults are strong predictors of overcoming the challenges of online game addiction, besides peer-group factors in adolescents, and neurobiological factors that influence the influence of internet gaming disorders. This literature review will discuss the influence of peer groups and neurobiological factors that underlie the expenditure of internet games in their teens.